Effect of basal insulin therapy on vascular endothelial function and adipokine profiles in people with Type 2 diabetes. Issue 12 (30th May 2016) - Makino, H.; Tanaka, A.; Hosoda, H.; Koezuka, R.; Tochiya, M.; Ohata, Y.; Tamanaha, T.; Miyamoto, Y.; Kangawa, K.; Kishimoto, I.
Abstract: Aim: To compare the effects of the basal insulin analogues glargine and detemir on endothelial function and adipocytokine levels in people with Type 2 diabetes. Methods: We studied 32 people with Type 2 diabetes whose blood glucose control was unsatisfactory while receiving only oral hypoglycaemic drugs. Participants were randomized to either insulin glargine or detemir for 24 weeks and then crossed over to the other treatment without a washout period. Flow‐mediated vasodilatation, adipocytokine levels (plasminogen activator inhibitor‐1 and leptin/adiponectin ratio), and fasting ghrelin levels were monitored. Results: HbA1c levels were significantly decreased by both basal insulin therapies. Body weight was significantly increased by glargine but not by detemir. The proportion of flow‐mediated vasodilatation was significantly increased by detemir but not glargine (glargine: from 5.17 ± 0.69 to 5.94 ± 0.83%; detemir: from 4.89 ± 0.78 to 7.92 ± 0.69%). Plasminogen activator inhibitor‐1 level was significantly decreased by only detemir (glargine: from 16.4 ± 1.8 to 17.3 ± 2.1; detemir: from 19.2 ± 2.8 to 16.0 ± 1.6 ng/ml). The leptin/adiponectin ratio was significantly increased only by glargine. Acyl ghrelin level was significantly decreased by glargine but not detemir. Conclusions: These results suggest that the effect on endothelial function and adipocytokine profiles may differ between glargine and detemir in people with diabetes (Trial registration ID: UMIN000004973). What's new?: The magnitude of the improvement in flow‐mediated vasodilatation with glargine treatment was smaller than that obtained with detemir, suggesting that the two compounds might differ in terms of their effect on atherosclerosis progression. Detemir treatment significantly decreased plasminogen activator inhibitor‐1 level, whereas glargine treatment did not significantly change this. By contrast, glargine treatment significantly augmented leptin adiponectin ratio, whereas detemir treatment did not significantly change this. This is the first study to report that fasting acyl ghrelin level was decreased by glargine treatment, while acyl ghrelin level was not affected by detemir treatment.